Halogenation of graphene with chlorine, bromine, or iodine by exfoliation in a halogen atmosphere - Poh, Hwee Ling (2014)
Nanoarchitectonics on graphene implicates a specific and exact anchoring of molecules or nanoparticles onto the surface of graphene. One such example of an effective anchoring group that is highly reactive is the halogen moiety. Herein we describe a simple and scalable method for the introduction of halogen (chlorine, bromine, and iodine) moieties onto the surface of graphene by thermal exfoliation/reduction of graphite oxide in the corresponding gaseous halogen atmosphere. We characterized the halogenated graphene by using various techniques, including scanning and transmission electron microscopy, Raman spectroscopy, high-resolution X-ray photoelectron spectroscopy, and electrochemistry. The halogen atoms that have successfully been attached to the graphene surfaces will serve as basic building blocks for further graphene nanoarchitectonics.